Enhanced cellular infiltration of human adipose-derived stem cells in allograft menisci using a needle-punch method. Issue 1 (December 2016) - Nordberg, Rachel; Charoenpanich, Adisri; Vaughn, Christopher; Griffith, Emily; Fisher, Matthew; Cole, Jacqueline; Spang, Jeffrey; Loboa, Elizabeth
Abstract Background The meniscus plays a crucial role in knee joint stability, load transmission, and stress distribution. Meniscal tears are the most common reported knee injuries, and the current standard treatment for meniscal deficiency is meniscal allograft transplantation. A major limitation of this approach is that meniscal allografts do not have the capacity to remodel and maintain tissue homeostasis due to a lack of cellular infiltration. The purpose of this study was to provide a new method for enhanced cellular infiltration in meniscal allografts. Methods Twenty medial menisci were collected from cadaveric human sources and split into five experimental groups: (1) control native menisci, (2) decellularized menisci, (3) decellularized menisci seeded with human adipose-derived stem cells (hASC), (4) decellularized needle-punched menisci, and (5) decellularized needle-punched menisci seeded with hASC. All experimental allografts were decellularized using a combined method with trypsin EDTA and peracetic acid. Needle punching (1-mm spacing, 28 G microneedle) was utilized to improve porosity of the allograft. Samples were recellularized with hASC at a density of 250 k/g of tissue. After 28 days of in vitro culture, menisci were analyzed for mechanical, biochemical, and histological characteristics. Results Menisci maintained structural integrity and material properties (compressive equilibrium and dynamic moduli) throughout preparations. Increased DNA content was observed in the needle-punched menisci but not in the samples without needle punching. Histology confirmed these results, showing enhanced cellular infiltration in needle-punched samples. Conclusions The enhanced infiltration achieved in this study could help meniscal allografts better remodel post-surgery. The integration of autologous adipose-derived stem cells could improve long-term efficacy of meniscal transplantation procedures by helping to maintain the meniscus in vivo.